Wielojęzyczność w polskim kontekście edukacyjnym - Wojciechowska, Bernadetta (Neofilolog, 2010)
The paper focuses on the discussion on the development of multilingualism in Polish educational context whose distinctive features are: the domination of the Polish language, low percentage of immigrants, and relatively sparse national minorities. Because of this evident distinctness of the Polish situation in the aforementioned domain, the didactic proposals prepared within European projects are analyzed in a critical way. Moreover, an attempt is undertaken to define the aims and the motivation that would take into consideration the characteristics of Polish educational context. On the basis of the definition of multilingual competence, the article aims to define certain basic foundations of multilingual education in Polish schools. Among other proposals, the central one is a postulate of departing from „monolingual methodics” that is from teaching successive languages in isolation from other learned languages (the native tongue included).